PENGARUH PENGAWASAN MELEKAT, PENGAWASAN FUNGSIONAL, PENGAWASAN PREVENTIF, PENGAWASAN DETEKTIF DAN PENGANGGARAN BERBASIS KINERJA TERHADAP EFEKTIFITAS PENGENDALIAN ANGGARAN (Studi Empiris pada SKPD Kabupaten Indragiri Hilir) - Tri Desi Arini; Edfan Darlis; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
the research aims to examine The Influence of supervision attached, monitoring functional, preventive supervision, detective supervision and performance-based budgeting to the effectiveness of budgetary control. Object of this research is department of the city government in Indragiri Hilir. There are sixty four which are sent but, only sixty questionnaires returned. The variables were examined are Influence of supervision attached, monitoring functional, preventive supervision, detective supervision and performance-based budgeting to the effectiveness of budgetary control. The results of this research showed that supervision attached has an effect on effectiveness of budgetary control with 0,031 significance, the monitoring functional has an effect on effectiveness of budgetary control with 0,19 significance, preventive supervision has an effect on effectiveness of budgetary control with 0,017 significance, detective supervision has an effect on effectiveness of budgetary control with 0,14 significance, and performance-based budgeting has no effect on effectiveness of budgetary control with 0,65 significance. The results of this research also showed that coefficient determinant is 92,8%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well.Keywords: attached, monitoring functional, preventive, detective and performance-based budgeting to the effectiveness of budgetary control